Antithrombin-III for New Coronavirus Infection (COVID-19) Under Conditions of Extracorporeal Membrane Oxygenation (Clinical Observation) - S. V. Zhuravel; V. V. Vladimirov; P. V. Gavrilov; I. V. Ivanov; S. S. Petrikov; K. A. Popugayev; A. M. Talyzin (Неотложная медицинская помощь, 2022)
COVID-19 is a disease that, in addition to respiratory failure, leads to thrombosis and bleeding due to coagulation disorders. Extracorporeal membrane oxygenation (ECMO), required in cases of a deterioration of gas exchange function of the lungs, contributes to changes in blood coagulation indicators, which leads to an increased risk of hemorrhagic complications and thrombosis. In the article, a clinical case of a severe course of COVID-19 is reported, which required ECMO. During the treatment, antithrombin-III was used, which allowed avoiding life-threatening complications and successfully completing the procedure.